Effectiveness and safety of povidone iodine for prolonged lung air-leak after lung surgery. (March 2022) - Chaari, Zied; Hentati, Abdessalem; Ben Ayed, Aimen; Abid, Walid; Frikha, Imed
Background: Pulmonary surgery is often associated with postoperative prolonged parenchymal air-leak. The purpose of this study was to determine efficacy and safety of povidone iodine as treatment of prolonged parenchymal air-leak following all-types of lung surgery. Methods: This prospective trial was conducted from June 2019 to December 2020, and designed under PanAfrican Clinical Trials Registry requirements. Patients having prolonged parenchymal air-leak were randomly allocated to povidone iodine protocol (Group A) or surveillance without povidone iodine (Group B). We collected the number of povidone iodine injections required before bubbling stopped, total drainage period, tolerance after injection, complications and side-effects. Comparative study was performed to evaluate povidone iodine efficacy. Results: Following randomization, Group A included 19 patients, and Group B 21. Both groups were comparable. The mean drainage period was 9.21 days in Group A (6–14 days) and 15.62 days in Group B (7–31 days) ( p  = 0.001). The mean hospitalization period was 11.05 days in Group A (7–16 days) and 18.9 days in Group B (9–38 days) ( p  < 0.0001). The mean follow-up period was 6.8 months (3–18 months). No deaths were noted in either groups. Four side-effects were reported in Group A (21%) and four serious complications were noticed in Group B (19%). No recurrences were reported in Group A versus one recurrence of homolateral pneumothorax in Group B (4.76%). Conclusions: Povidone iodine is an effective and safe solution for pleurodesis. It is associated with a low complication rate that remains acceptable, and could be proposed as treatment of prolonged parenchymal air-leak after lung resections.